Prescription Drugs and the Hazard of Addiction - A. Alzayed (Emerging Trends in Drugs, Addictions, and Health)
Introduction: It has been a known fact that prescription drugs make up a considerable portion of drug addiction in any community. It has estimated to form up to 60% of addict population in some countries. Methods: Accordingly, it is of great significance to discuss this medical and legal issue in a scientific approach, trying to figure which drugs are at a greater risk to be abused by patients who have the suspect ability to be addicted to any substance. Results: Try to develop a system that is able to prevent or at least reduces the risk. Conclusions: This speech aims to construct a frame to address these points.